EFFECTS OF EARLY WEANING AND TEMPORARY CALF REMOVAL ON BEEF COW REPRODUCTION AND CALF GROWTH - GOTTSCHALL, CARLOS SANTOS (1999)
The effects of early weaning (EW) and temporary calf remova' (TCR) on beef cattle cows and their calvos wereevaluated. Also were assessed: the weight at beginning of the breeding season (WBBSc), the weight at beginning of the earlyweaning (WEWc), the weight at the end of breeding season (WEBSc), the final weight (FWc), the average daily gain (ADGc),and the pregnancy rate (PR), for the cows. It was evaluated the early weaning weight (EWWcalf), the weight at the end of thetrial (Ewcalf), and the average daily gain (ADGcalf), for the calves submitted to EW or TCR. The breeding season started at 12/01/97 and finished at 02/28/98. The EW was measured at 01/03/98, and the TCR at 12/02/97, 01/03/98, and 02/03/98. WBBSc,WEWc, WEBSc, and FWc were 427.0 and 446.9 kg, 432.9 and 343.9 kg, 464.0 and 452.4 kg, 472.5 and 435.5 kg, for the cowssubmitted to EW and TCR, respectively, with no significance (P>0.05). However, the ADGc, from 12/01/97 to 02/28/98, was0.421 and 0.059 kg/day to the EW and TCR, respectively (P< 0.01). The PR was 90%, for the EW group, and 23.8 %, for theTCR group (P<0.01). The Ewcalf was 143.1 and 172.1 kg, for the EW and TCR groups, respectively, (P<0.01). The ADGcalfwas 0.237 and 0.532 kg/day (P<0.01), respectively, for calves submitted to EW or TCR group. The cows submitted to EWshowed a higher PR and ADGc. However, the calves in the TCR group showed higher Ewcalf and AVDcalf than the EW calves.